2015
DOI: 10.1097/j.pain.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C gamma-mediated phosphorylation of GluA1 in the postsynaptic density of spinal dorsal horn neurons accompanies neuropathic pain, and dephosphorylation by calcineurin is associated with prolonged analgesia

Abstract: Loss of calcineurin (protein phosphatase 3) activity and protein content in the post-synaptic density (PSD) of spinal dorsal horn neurons was associated with pain behavior following chronic constriction injury (CCI) of the rat sciatic nerve, and intrathecal administration of the phosphatase provided prolonged analgesia (Miletic et al., Pain 2013;154:2024-2033). In this study we examined if one consequence of the loss of calcineurin was the persistent phosphorylation of the GluA1 subunit of α-amino-3-hydroxy-5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
(51 reference statements)
0
18
0
Order By: Relevance
“…Furthermore, recent research revealed that H89, a PKA (encoded by the Prkaca gene) inhibitor and GF109203X, a PKCγ (encoded by the Prkcg gene) inhibitor suppresses TRPV1 externalization in DRGs sensory neuron cultures [ 35 ] and that the latter compound is also able to reverse capsaicin-induced pain-related behaviour in MIA rats [ 36 ]. Decreases of Mapk14 and Prkcg mRNA levels following FAAH inhibition highlights hopes for new treatment strategies of neuropathic components in rheumatic diseases, as seen with intrathecal administration of p38α MAPK and PKCγ inhibitors in a chronic constriction injury model of neuropathic pain [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent research revealed that H89, a PKA (encoded by the Prkaca gene) inhibitor and GF109203X, a PKCγ (encoded by the Prkcg gene) inhibitor suppresses TRPV1 externalization in DRGs sensory neuron cultures [ 35 ] and that the latter compound is also able to reverse capsaicin-induced pain-related behaviour in MIA rats [ 36 ]. Decreases of Mapk14 and Prkcg mRNA levels following FAAH inhibition highlights hopes for new treatment strategies of neuropathic components in rheumatic diseases, as seen with intrathecal administration of p38α MAPK and PKCγ inhibitors in a chronic constriction injury model of neuropathic pain [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that PKC-mediated phosphorylation of the IP 3 R1 may form part of a positive feedback loop. Activated PKCγ phosphorylates TRPC3-channels which reduces Ca 2+ influx from the plasma membrane through these channels and limits the Ca 2+ concentration in the cytoplasm [ 29 , 87 ]. As discussed above, one mutation related to SCA14 was recently shown to result in a constitutive active form of PKCγ causing abnormal dendritic development of Purkinje cells linking an increased PKC activity to the pathogenesis of ataxia [ 45 ].…”
Section: Ip3r1 Car8 and Pkcγ Are Active In A Common Signaling Pathwamentioning
confidence: 99%
“…The molecular mechanism of PKCα-dependent upregulation of CP-AMPARs includes the activation of PKCα under painful conditions as an upstream trigger for the AMPAR protein phosphorylation, a subsequent disrupting of the receptor binding to its synaptic anchoring protein, followed by receptor’s internalization 5 . Multiple sites for the PKC-mediated phosphorylation of AMPAR subunits have been distinguished: serine residue S880 for GluA2 5 , S831 27 , S818, and S816 for GluA1 28 30 that opens considerations for multiple involvement of different PKC enzyme isoforms in both inflammatory pain development and maintenance.…”
Section: Discussionmentioning
confidence: 99%